2022
DOI: 10.3390/v14081810
|View full text |Cite
|
Sign up to set email alerts
|

Using Self-Assembling ADDomer Platform to Display B and T Epitopes of Type O Foot-and-Mouth Disease Virus

Abstract: Foot-and-mouth disease virus (FMDV) is a highly contagious and devastating virus that infects cloven-hoofed livestock and various wildlife species. Vaccination is the best measure to prevent FMD. ADDomer, as a kind of non-infectious adenovirus-inspired nanoparticle, has the advantage of high thermal stability. In this study, two dominant B-cell antigen epitopes (residues 129~160 and 200~213) and a dominant T-cell antigen epitope (residues 16~44) of type O FMDV were inserted into the ADDomer variable loop (VL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…We and others have shown that a range of peptides and small protein domains can be inserted into the VL and RGD loops of the PBP 16,17,19,20,30 Chimera AH0 from our human Ad3 derived ADDobody-AH0 (Fig. 4A).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…We and others have shown that a range of peptides and small protein domains can be inserted into the VL and RGD loops of the PBP 16,17,19,20,30 Chimera AH0 from our human Ad3 derived ADDobody-AH0 (Fig. 4A).…”
Section: Discussionmentioning
confidence: 80%
“…We and others have shown that a range of peptides and small protein domains can be inserted into the VL and RGD loops of the PBP 16,17,19,20,30 . Moving forward, based on our results, we can now conceivably generate a synthetic ADDobody library with randomized VL and RGD loops that can be used for ribosome display in vitro selection and evolution experiments against any target of choice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ADDomer was shown to drain to lymph nodes and is efficiently taken up by antigen presenting cells 28 . Successful presentation of T cell epitopes, in addition to B cell epitopes, by ADDomer has been demonstrated recently for Type O foot-and-mouth disease virus, resulting in protective responses against the viral pathogen 45 . A range of T cell epitopes in the SARS-CoV-2 proteome have been identified.…”
Section: Discussionmentioning
confidence: 99%